2012
DOI: 10.2337/dc11-2396
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Phthalate Metabolites Are Associated With Prevalent Diabetes in the Elderly

Abstract: OBJECTIVEPhthalates are ubiquitous industrial high-volume chemicals known as ligands to peroxisome proliferator–activated receptors (PPARs). Because PPAR-γ agonists modulate insulin sensitivity and are used to treat type 2 diabetes, we investigated whether circulating levels of phthalate metabolites are related to prevalent type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 1,016 subjects, aged 70 years, were investigated in the Prospective Investigation of the Vasculature in Uppsala Seniors Study. Four pht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(99 citation statements)
references
References 35 publications
1
95
1
2
Order By: Relevance
“…Several epidemiologic studies have found associations between exposure to bisphenol A (BPA) and diabetes (Sun et al, 2014;Lang et al, 2008;Melzer et al, 2010;Silver et al, 2011;Shankar and Teppala, 2011). Phthalates have also been associated with type 2 diabetes (Sun et al, 2014) and insulin resistance (James-Todd et al, 2012;Lind et al, 2012;Stahlhut et al, 2007) in human populations. However, there are limited epidemiologic data assessing the risk of metabolic dysfunction associated with exposure to endocrine disrupting chemicals during pregnancy (Ettinger et al, 2009;Robledo et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Several epidemiologic studies have found associations between exposure to bisphenol A (BPA) and diabetes (Sun et al, 2014;Lang et al, 2008;Melzer et al, 2010;Silver et al, 2011;Shankar and Teppala, 2011). Phthalates have also been associated with type 2 diabetes (Sun et al, 2014) and insulin resistance (James-Todd et al, 2012;Lind et al, 2012;Stahlhut et al, 2007) in human populations. However, there are limited epidemiologic data assessing the risk of metabolic dysfunction associated with exposure to endocrine disrupting chemicals during pregnancy (Ettinger et al, 2009;Robledo et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Estos químicos son parte de la materia prima principal en la fabricación de plástico. Existen reportes que sugieren una relación entre los ftalatos y la diabetes, obesidad y resistencia a la insulina (114). Estudios in vitro, indican que afectan la regulación del RI, la oxidación de la glucosa en células hepáticas y en general la homeostasis de la glucosa (115).…”
Section: Los Policlorobifenilos (Pcb) O Bifenilos Policloradosunclassified
“…They could act also via PPARa and PPARa-independent pathways [30]. PAE also seem to be involved in the pathogenesis of insulin resistance [31], obesity [32], and T2DM [33].…”
Section: Phthalates (Paes)mentioning
confidence: 99%